ANTI-PSYCHOTICS INDUCED SEXUAL DYSFUNCTION - Khan, Aftab Alam; Nawaz, Haq; Nazneen, Zainab; Yousafzai, Aziz Ur-Rehman (Pakistan Journal of Physiology, 2017)
Background: Sexual dysfunction associated with the use of antipsychotic drugs is quite prevalent affecting the patients’ quality of life and one of the reasons for non-compliance. This important aspect is underestimated and overlooked by the treating professionals, partly because patients rarely talk about their dysfunction. Due to the scarcity of local data on the subject the objective of the present study was to explore and compare the prevalence of sexual dysfunction associated with antipsychotic drugs. Methods: This was a hospital-based cross-sectional study comprising of comparative assessment among five antipsychotics being consumed by 91 male patients under this study. Results: Risperidone, haloperidol and olanzapine collectively as a group were associated with increased incidence of sexual dysfunction (42.43%) compared to quetiapine and aripiprazole group (16%) which was statistically significant. Individually risperidone (48%) and haloperidol (45.81%) were associated with highest incidence of sexual dysfunction followed by olanzapine (29.41%). Quetiapine (16.67%) and aripiprazole (15.38%) were associated with the lowest incidence of sexual dysfunction. Conclusion: Risperidone and haloperidol are associated with a higher rate of sexual dysfunction compared to olanzapine. Quetiapine and aripiprazole have a significantly lower profile of adverse effects on sexual function. Pak J Physiol 2017;13(3):3–7